Depreciation Bases of Equipments Used for Construction of Cross Country Pipelines: A Rational and Systematic Framework - Jain, P. K.; Choudhury, D. K.; Jindal, Sunita (Indian Journal of Finance, 2014)
In cross country pipeline projects, pipelines are constructed with the help of particular types of plant and machinery subject to depreciation in the process of being used for the construction work. The present study (empirical in nature) identified and selected the equipments which play a key role in construction of pipelines. The present work is based on collection of data pertaining to useful life and rate of depreciation of pipeline construction equipments from 12 equipment users in the country. The data were analyzed with the application of statistical tool and SPSS software. For pipeline construction agencies, depreciation is considered as a part of the cost of construction of projects. The present study reported that depreciation needs to be charged on pipeline construction equipments.